Immuno-informatics voyage through molecular mimicry of Heat Shock Proteins: Potential IBD immunopathogenesis - Mahsa Alem; Seyyed Meysam Abtahi Froushani; Nasim Hajighahramani; Saied Hosseini-Asl; Farhad Pourfarzi; Rasoul Nemati (PLoS ONE, 2025)
Background The interplay between the gut microbiota axis and host immunity is pivotal in the pathogenesis of inflammatory bowel disease (IBD), an idiopathic inflammatory condition. Molecular mimicry may be at the root of autoimmune and auto-inflammatory diseases, such as IBD, when microbial antigens and host proteins share structural and molecular similarities. However, auto-inflammation can also occur through mechanisms independent of molecular mimicry. The present study focused on the possible involvement of intestinal bacterial heat shock proteins (HSPs) in the immunopathogenesis of IBD as a cutting-edge issue. Methods We employed an immuno-informatics approach to evaluate host-microbe interactions and predict the involvement of bacterial HSPs 60, 70, and 90 in IBD via molecular mimicry as our primary objective. The substantial evolutionary conservation of HSPs and their presence in inflammation scenarios propelled our research. To validate our approach, we performed docking and molecular dynamics (MD) simulations on selected HLA-epitope complexes. Results Our analysis revealed that all studied bacteria, compared to Homo sapiens, exhibited meaningful sequence similarity and identity of HSPs. Thirteen bacterial species and their corresponding thirteen epitopes derived from HSP counterparts were selected for further investigation. Finally, a specific epitope of human HSP60 and three epitopes of HSP70 demonstrated considerable sequence similarity to their bacterial counterparts, which was further corroborated through MD simulations as a primary outcome. The secondary outcomes encompassed various factors, including assessing residues in the epitope and receptor-binding grooves within the epitope-HLA complex. Based on the secondary data analysis, the co-expression findings suggested that HSP70 could serve as epitopes in eliciting T-cell-mediated autoimmune responses during infections. Conclusion The study provided evidence of molecular mimicry between microbial and human HSPs, which could serve as molecular targets for cross-reactive T cells. In addition to considering sequence similarity, our study emphasized the importance of structural interactions as essential factors in cell signaling and immunological pathways.